Phenotypical spectrum of DOK7 mutations in congenital myasthenic syndromes. - Müller, J; Herczegfalvi, A; Vilchez, J; Colomer, J; Bachinski, L; Mihaylova, V; Santos, M; Schara, U; Deschauer, M; Shevell, M; Poulin, C; Dias, A; et al. (2007)
Dok ('downstream-of-kinase') family of cytoplasmic proteins play a role in signalling downstream of receptor and non-receptor phosphotyrosine kinases. Recently, a skeletal muscle receptor tyrosine kinase (MuSK)-interacting cytoplasmic protein termed Dok-7 has been identified. Subsequently, we and others identified mutations in DOK7 as a cause of congenital myasthenic syndromes (CMS), providing evidence for a crucial role of Dok-7 in maintaining synaptic structure. Here we present clinical and molecular genetic data of 14 patients from 12 independent kinships with 13 different mutations in the DOK7 gene. The clinical picture of CMS with DOK7 mutations is highly variable. The age of onset may vary between birth and the third decade. However, most of the patients display a characteristic 'limb-girdle' pattern of weakness with a waddling gait and ptosis, but without ophthalmoparesis. Respiratory problems were frequent. Patients did not benefit from long-term therapy with esterase inhibitors; some of the patients even worsened. DOK7 mutations have emerged as one of the major genetic defects in CMS. The clinical picture differs significantly from CMS caused by mutations in other genes, such as the acetylcholine receptor (AChR) subunit genes. None of the patients with DOK7 mutations had tubular aggregates in the muscle biopsy, implying that 'limb-girdle myasthenia (LGM) with tubular aggregates' previously described in literature may be a pathogenic entity distinct from CMS caused by DOK7 mutations.